Relation between vault difficulty values and biomechanical parameters in men's artistic gymnastics - Atikovic, A.; Smajlovic, N. (Science of Gymnastics Journal, 2011)
The aim of the paper is to define which biomechanical parameters explain and define the difficulty vault value. The study sample included 64 vaults from the Code of Points (COP) of the International Gymnastics Federation (FIG, 2009). The dependent variable included all difficulty values ranging from 2-7.2 points, while the sample of independent variables included 12 biomechanical variables (data was collected from the literature and our measurements). With regression analysis we explained 92.4% of the difficulty vault value. Only three biomechanical variables were predictors: degrees of turns around transversal axis, degrees of turns around longitudinal axis and body's moment of inertia around transversal axis in the second flight phase.